Exertion during a hypoxia altitude simulation test helps identify potential cardiac decompensation. Issue 7 (24th June 2019) - Seccombe, Leigh; Peters, Matthew; Farah, Claude
Abstract : A 64‐year‐old female with a history of chronic thromboembolic pulmonary arterial hypertension (CTEPH), moderate airway obstruction (forced expiratory volume in 1 second (FEV1 ) 58% predicted), and resting oxygen saturation below the normal range (SaO2 94%) underwent a hypoxic challenge test (HCT) to determine suitability for long‐haul air travel. The HCT showed only a mild decrease in SaO2 (89% at 0.15 fraction of inspired oxygen (FIO2 )) at rest. However, a HCT coupled with mild exercise at two metabolic equivalents demonstrated significant hypoxia (SpO2 77%) with worsening right ventricular impairment and an inability to increase cardiac output measured with echocardiography. The case highlights the importance of the evaluating cardiac and pulmonary reserve during hypoxic stress. Resting measures alone may not identify risk, and the addition of an exercise component was essential in this case. Abstract : We present the novel case of a 64‐year‐old female with a history of chronic thromboembolic pulmonary arterial hypertension and moderate bronchiectasis who experienced right ventricular failure during a clinically indicated flight simulation. While the subject recorded acceptable oxygenation during the simulation in resting conditions, echocardiography demonstrated underlying cardiopulmonary limitation that significantly worsened with mild exercise.